Луысал ке ваньзэ вераме: кылбуръёс, поэмаос / Николай Байтеряков - Байтеряков Николай Семенович (Удмуртия, 1992)
Экземпляры: ф.3 (1993) / Инвентарный номер: 36422 / Цена: / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: Б 18 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5^VLBC/RL